Neoadjuvant therapy to downstage the extent of resection of gastrointestinal stromal tumors - Jakob, Jens; Hohenberger, Peter (Visceral medicine, 2018)
Introduction: Gastrointestinal stromal tumors (GIST) are rare malignant tumors in terms of incidence, and they are not linked to specific symptoms. Often, primary tumors, particularly of the stomach, rectum, or rectovaginal space, are quite large when detected, and multivisceral resection seems to be the treatment of choice as the mainstay of therapy is complete tumor removal. If a gain-of-function mutation in the KIT gene is present, drug therapy with receptor tyrosine kinase inhibitors (RTKIs) might significantly downstage primary GIST tumors. Methods: A review of the literature was performed to identify the current evidence for preoperative treatment of GIST regarding toxicity, efficacy, and oncological outcome, including mutational data from our own database. Results: Four phase II as well as several cohort studies showed acceptable toxicity and no increased perioperative morbidity of preoperative imatinib. Progressive disease during preoperative treatment was a rare event, and partial response was achieved in 40-80% of all patients. For methodological reasons, the trials cannot prove an oncological long-term superiority of preoperative treatment. Conclusion: Preoperative therapy with imatinib is safe and recommended for patients with locally advanced GIST. Neoadjuvant imatinib therapy may enable less invasive and organ-sparing surgery, avoid tumor rupture during extensive resectional procedures, and improve the quality of perioperative RTKI treatment.